Relación de la temperatura, humedad relativa y precipitación en la fenología floral de poblaciones silvestres de Annona cherimola Mill. en la provincia de Loja - Elizalde Granda, Glenia del Cisne (2018)
In Ecuador, particularly in the province of Loja, there is a large number of ecotypes of A. cherimola with a wide genetic diversity, forming wild forests. This species, despite its wide diversity in the province of Loja and market acceptance, has not been studied, nor has it been taken advantage of from the economic point of view, nor from its biological potential, since there is no research and analysis of data on the phases phenological that contribute to the application of good agricultural practices. The characterization of the phenological events of the flowering of A. cherimola Mill, allowed to determine two stages with their respective phases; first stage 5 (emergence of flowering) in which the following phases are recorded: phase 50, floral buds closed and covered by brown scales, phase 51, beginning of swelling of flower buds; the scales begin to separate, phase 53 outbreak explosion; first scarcely visible floral primordium, phase 54, visible sepals; the petals begin to elongate and phase 59, flowers closed with petals completely elongated, forming a long corolla and the second stage 6 (flowering) in which the following phases are recorded: phase 60, prehembra, phase 61, female and the phase 65 male. The correlations between the duration of the floral phenology and the climatic variables of temperature, relative humidity and precipitation indicate that there is a strong positive correlation in the Chirimoyal (rs: 0.87 and p: 0.0103) and Nangora (rs=0.82, p= 0.024) sectors and a moderate positive correlation (rs : 0.7 and p: 0.0.378) in the Santa Teresa sector, for the variables relative humidity and temperature there is no correlation with the duration of the floral phenology of Chirimoya. Key words: Floral phenology, temperature, relative humidity, precipitatión